2005
DOI: 10.1083/jcb.200408064
|View full text |Cite
|
Sign up to set email alerts
|

PATJ regulates tight junction formation and polarity in mammalian epithelial cells

Abstract: Recent studies have revealed an important role for tight junction protein complexes in epithelial cell polarity. One of these complexes contains the apical transmembrane protein, Crumbs, and two PSD95/discs large/zonula occludens domain proteins, protein associated with Lin seven 1 (PALS1)/Stardust and PALS1-associated tight junction protein (PATJ). Although Crumbs and PALS1/Stardust are known to be important for cell polarization, recent studies have suggested that Drosophila PATJ is not essential and its fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
192
4
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(216 citation statements)
references
References 32 publications
12
192
4
5
Order By: Relevance
“…However, Adachi et al (24) showed that, despite its domain similarity, mPATJ, but not MUPP1, regulates TJ stability (24). These data are in line with previous findings describing TJ formation delay or defects upon loss of mPATJ in cultured epithelial cells (25,26). Other studies describe a role of mPATJ in Myosin-driven processes like apical constriction and cell migration (27)(28)(29).…”
supporting
confidence: 80%
“…However, Adachi et al (24) showed that, despite its domain similarity, mPATJ, but not MUPP1, regulates TJ stability (24). These data are in line with previous findings describing TJ formation delay or defects upon loss of mPATJ in cultured epithelial cells (25,26). Other studies describe a role of mPATJ in Myosin-driven processes like apical constriction and cell migration (27)(28)(29).…”
supporting
confidence: 80%
“…However, the recovered PATJ is mislocalized in the L379P cell line and the delC cell line (Supplemental Figure 2). Our laboratory has done a PATJ knockdown and has not observed adherens junction disruption (Shin et al, 2005). A separate PATJ knockdown study in Caco2 cells reported that PATJ knockdown leads to the mislocalization of PALS1, but no adherens junction defect followed the PATJ depletion and PALS1 mislocalization (Michel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These two effects on localization also yield distinct functional consequences. Evidence suggests that sequestered PDZ proteins are functionally inactivated because, in epithelial cells, E4-ORF1-induced sequestration of the PATJ polarity protein and ZO-2, which are critical for tight junction (TJ) biogenesis (Shin et al, 2005;Umeda et al, 2006), disrupts the TJ barrier function and causes a loss of apicobasal polarity (Latorre et al, 2005). In fibroblasts, sequestration of ZO-2 also blocks its tumor suppressor activity (Glaunsinger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%